The Succession of the Gut Microbiota in Insects: A Dynamic Alteration of the Gut Microbiota During the Whole Life Cycle of Honey Bees (Apis cerana) - Dong, Zhi-Xiang; Chen, Yi-Fei; Li, Huan-Yuan; Tang, Qi-He; Guo, Jun (Frontiers in Microbiology, 2021)
Asian honey bee Apis cerana is an valuable biological resource insect that plays an important role in the ecological environment and agricultural economy. The composition of gut microbiota has a great influence on the health and development of the host. However, studies on insect gut microbiota are rarely reported, especially on the dynamic succession of insect gut microbiota. Therefore, this study used high-throughput sequencing technology to sequence the gut microbiota of A. cerana at different development stages (0 day post emergence (0 dpe), 1 dpe, 3 dpe, 7 dpe, 12 dpe, 19 dpe, 25 dpe, 30 dpe, and 35 dpe). The results of this study indicated that the diversity of the gut microbiota had a significant impact on different developmental stages (Ace, P = 0.045; Chao, P = 0.031; Shannon, P = 0.0019; Simpson, P = 0.041). In addition, under the phylum and genus taxonomic units, the dominant microbiota in the gut microbiota changed significantly at different developmental stages. Our results also suggest that environmental exposure in the early stages of development has the greatest impact on gut microbiota. The results of this study reveal the general rule of gut microbiota succession in the insect life cycle. This study not only deeps our understanding of the colonization pattern of gut microbiota in worker bees but also provides useful information for exploring the colonization of gut microbiota in insects and other animals more comprehensively.